46. RESULTS OF REVERSE-FLOW ENDASTROSCOPY OF URTERELITAL STONES MIDDLE 1/3 AND LOWER 1/3 USING LASER - HOLMIUM ENERGY AT THAI BINH MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the results of treatment for ureteral stones middle 1/3 and lower 1/3 by retrograde lithotripsy using heavy Holmium laser power at Thai Binh Medical University Hospital.Methods: Cross-sectional descriptive study of 73 patient underwent ureteral lithotripsy middle 1/3 and lower 1/3 using the internal countercurrent lithotripsy method using Holmium laser energy at Thai Binh Medical University Hospital from January 2021 to June 2023. Recording data on disease characteristics; ureteral stone dissolution time; complications and outcomes.Results: The average age was 54,4±11,43 years old, men accounted for 64.4%, women accounted for 35.6%. Dull pain in the lumbar region and renal colic are the main reasons why patients go to the hospital (accounting for 57.6%). Most patients have stone dissolution time
Keywords: Ureteral lithotripsy; Retrograde endoscopy; laser – holmium